Microsoft Office Groove 2007 step by step - Jewell, Rick (Microsoft Press, 2008)
A guide to Microsoft Office Groove covers such topics as creating collaborative workspaces, capturing and sharing data, setting up online discussion boards, sending instant messages and alerts, and publishing and synchronizing documents.
Includes index. - Print version record
Keywords: Microsoft Office Groove; Teams in the workplace; Virtual work teams; Business -- Communication systems; Microsoft Office Groove (Computer software); Équipes de travail; Équipes virtuelles; Affaires; Systèmes de communication; BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development; BUSINESS & ECONOMICS; Workplace Culture; Business; Communication systems